For Reducing Energy Consumption in Public Transportation (European Journal of Marketing and Economics, 2024)
The concept of sustainable development, applied to cities, leads necessarily to give a large place to pedestrians, to cyclists and to public transport, which returns the viability to cities, by eliminating the enlargement of cars number, urban sprawl, accidents, traffic, pollution, and especially the huge consumption of energy, caused by cars and private transport. Mobility problems (traffic, transport...) are became more and more important, to study and resolve, because of their highest consumption of energy. Our research task is focused especially on the road transport of passengers, because it is a mode very large-scale consumer of energy which is often aimed by the energy policies. This leads us to study the dependence between energy and transport, then to study the intramodality of transport by encouraging public transport. But for that the passengers leave their cars and move towards public transport, this requires the development of a high-quality public transport, which is conquering with that of private vehicles, and therefore moderate the high consumption of energy. For that one of an important problem of stop location especially in the big cities is set.
Keywords: Public transportation, Petroleum, Energy demand, Operational research.